Restrictive Transfusion Strategy Is More Effective in Massive Burns: Results of the TRIBE Multicenter Prospective Randomized Trial. (21st March 2019) - Palmieri, Tina L; Holmes, James H; Arnoldo, Brett; Peck, Michael; Cochran, Amalia; King, Booker T; Dominic, William; Cartotto, Robert; Bhavsar, Dhaval; Tredget, Edward; Stapelberg, Francois; Mozingo, David; et al.
Abstract: Objectives: Studies suggest that a restrictive transfusion strategy is safe in burns, yet the efficacy of a restrictive transfusion policy in massive burn injury is uncertain. Our objective: compare outcomes between massive burn (≥60% total body surface area (TBSA) burn) and major (20–59% TBSA) burn using a restrictive or a liberal blood transfusion strategy. Methods: Patients with burns ≥20% were block randomized by age and TBSA to a restrictive (transfuse hemoglobin <7 g/dL) or liberal (transfuse hemoglobin <10 g/dL) strategy throughout hospitalization. Data collected included demographics, infections, transfusions, and outcomes. Results: Three hundred and forty-five patients received 7, 054 units blood, 2, 886 in massive and 4, 168 in restrictive. Patients were similar in age, TBSA, and inhalation injury. The restrictive group received less blood (45.57 ± 47.63 vs. 77.16 ± 55.0, p < 0.03 massive; 11.0 ± 16.70 vs. 16.78 ± 17.39, p < 0.001) major). In massive burn, the restrictive group had fewer ventilator days ( p < 0.05). Median ICU days and LOS were lower in the restrictive group; wound healing, mortality, and infection did not differ. No significant outcome differences occurred in the major (20–59%) group ( p > 0.05). Conclusions: A restrictive transfusion strategy may be beneficial in massive burns in reducing ventilator days, ICU days and blood utilization, but does not decrease infection, mortality, hospital LOS or wound healing.